1985
DOI: 10.1104/pp.79.3.635
|View full text |Cite
|
Sign up to set email alerts
|

Control by Ethylene of Arginine Decarboxylase Activity in Pea Seedlings and Its Implication for Hormonal Regulation of Plant Growth

Abstract: Activity of arginine decarboxylase in etiolated pea seedlings appears 24 hours after seed imbibition, reaches its highest level on the 4th day, and levels off until the 7th day. This activity was found in the apical and subapical tissue of the roots and shoots where intensive DNA synthesis occurs. Exposure of the seedlings to ethylene greatly reduced the specific activity of this enzyme. The inhibition was observed within 30 min of the hormone application, and maximal effect-90% inhibition-after 18 hours. Ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 21 publications
0
30
1
1
Order By: Relevance
“…These findings contrast with the results from the deepwater rice system (3), where significant accumulation of spermidine was observed in response to ethylene, but putrescine showed only a relatively small increase. The observation that in etiolated pea seedlings polyamine biosynthesis is inhibited by ethylene shows even more of a contrast (1). Moreover, ethylene inhibits growth in pea, whereas it promotes growth in both types of rice.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These findings contrast with the results from the deepwater rice system (3), where significant accumulation of spermidine was observed in response to ethylene, but putrescine showed only a relatively small increase. The observation that in etiolated pea seedlings polyamine biosynthesis is inhibited by ethylene shows even more of a contrast (1). Moreover, ethylene inhibits growth in pea, whereas it promotes growth in both types of rice.…”
Section: Discussionmentioning
confidence: 94%
“…In the experiment under sealed conditions, 10 seedlings were transferred into a 30-mL flask with 2 mL of 10' M Mes buffer solution (pH 5.5), and the flasks were sealed with silicone rubber caps. Ethylene treatment was administered by injecting 3 mL of 10 gL/L ethylene into the sealed containers to make a concentration of 1 Figure 2. In aerobic controls, putrescine concentra- tion increased gradually within the initial 2 d of treatment and decreased subsequently ( Fig.…”
Section: Materials and Methods Plant Materials And Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free polyamines inhibited ethylene production in a variety of tissues (2,5,8,24) opposite effects in relation to fruit ripening and senescence (3,5,9,22,26). Because of this, polyamine and ethylene physiologies may be linked during fruit development.…”
Section: Introductionmentioning
confidence: 97%
“…Polyamines and ethylene biosynthetic pathways are competitive: when specific inhibitors are used to prevent either ethylene or spermidine biosynthesis, the flow of carbon atoms from SAM through the alternative pathway is favoured [20,39]. Still, exogenously applied polyamines inhibit the plant's ability to produce ethylene [1] and, conversely, exogenous ethylene suppresses the accumulation of polyamines [2]. It has been shown that polyamines have the potential to regulate ethylene biosynthesis by affecting the accumulation of ACC synthase transcripts [19].…”
Section: Introductionmentioning
confidence: 99%